2007
DOI: 10.1017/s0025315407054586
|View full text |Cite
|
Sign up to set email alerts
|

Abundance estimate and seasonal patterns of grey seal (Halichoerus grypus) occurrence in Brittany, France, as assessed by photo-identification and capture–mark–recapture

Abstract: Abundance estimate and seasonal patterns of grey seal (Halichoerus grypus) occurrence in Brittany, France, as assessed by photo-identification and capture-mark-recapture It has been suggested that the large grey seal colonies around the British Isles form local populations within a metapopulation, and that seal movements outside the breeding season lead to considerable overlap between individual home ranges. Individual behaviour and population dynamics of small peripheral colonies may also play a role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The geometric mean of the MLEs of the survival probabilities at NR is 0.882. This is lower than the time-independent survival estimates of 0.98 for a southern North Sea colony (Gerondeau et al 2007), and 0.96 (estimated for Norwegian grey seals, Wiig 1991). It appears therefore that the survival probability at NR is generally lower than for grey seals at a number of different locations in several other studies, and may be a large contributing factor in the observed downward trend in pup production at this colony over the time scale of the study (Duck and Mackey 2005).…”
Section: Discussionmentioning
confidence: 54%
“…The geometric mean of the MLEs of the survival probabilities at NR is 0.882. This is lower than the time-independent survival estimates of 0.98 for a southern North Sea colony (Gerondeau et al 2007), and 0.96 (estimated for Norwegian grey seals, Wiig 1991). It appears therefore that the survival probability at NR is generally lower than for grey seals at a number of different locations in several other studies, and may be a large contributing factor in the observed downward trend in pup production at this colony over the time scale of the study (Duck and Mackey 2005).…”
Section: Discussionmentioning
confidence: 54%
“…Because of the heavily biased ratio of males in our sample, we could not explore gender-based differences in distribution patterns, although such differences are known to occur in this species, potentially reducing intra-specific competition (Breed et al 2006). Most adult females are known to leave MOL during the breeding season (Gerondeau et al, 2007), which is consistent with the very low pup production. While the number of tracked adult females from MOL was too low in our study to identify their breeding sites, one grey seal female photographed at MOL during summers 1998 to 2000 was previously photo-identified while breeding in the Blasket islands, western Ireland, in mid November 1996 (O. O'Cadhla & L. Hiby, pers.…”
Section: Distribution and Connectivitymentioning
confidence: 89%
“…A small population of less than 200 individuals uses haul-out sites in Brittany, France [36], [40], [60], [61] which is further south than predicted. This sub-population inhabit water slightly warmer than the 95% range of mean SST but the average summer temperature is well within the 95% range of the in situ recorded SST values from the 81 seals in the sample used here.…”
Section: Discussionmentioning
confidence: 99%